Occupational medicine in taking over work injuries from family practice : a one-year follow-up - Lalić, Hrvoje, liječnik, 1960- (Array, 2009)
Abstract: Occupational medicine has taken over from Family practice the treatment of work injuries and occupational diseases in the Republic of Croatia since January 1, 2008. The reason was too many long-lasting sick leaves which general practitioners were unable to curb adequately. The research objective was to show the results of the one-year follow-up of the carried out reform, i.e. the efficiency of Occupational medicine in the new function. The methods of data comparison and McNemar statistics were used of one-year follow-up in an Occupational medicine surgery that cares for 5800 employees in Littoral-Mountainous County. From 32 patients in February 2008, 30 work injuries and 2 occupational diseases, the overall number diminished in February 2009 to 13 patients with work injuries and no diagnosed occupational disease, p<0.001 for work injuries. Also the number of patients on sick leave over three months fell from 14 to 4. Occupational medicine has proved to be more efficient than Family practice in assessing sick leave. This does not mean that family practice, due to a number of reasons mentioned in the research, is of less importance. For the patient can always return to his general practitioner for further treatment, and sick leave if necessary, but not on the grounds of work injury and occupational disease